Media Framing, Corporate Logic and the Public Image of Pesantren in the Xpose Uncensored Trans7 Controversy - Mahfudz Mahfudz; Khazri bin Osman; Farhan Farhan (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines how pesantren, kiai, and santri were represented in the Xpose Uncensored Trans7 controversy aired on October 13, 2025, and how such representation was shaped by corporate media logic. Employing a critical qualitative case-study design, the research analyzed the pesantren-related broadcast segment using an integrated framework of content analysis, framing analysis, critical discourse analysis, and political economy of media. Primary data were drawn from the broadcast segment, while secondary data included media reports, public responses, institutional statements, regulatory materials, and relevant academic literature. The analysis focused on verbal narration, visual sequencing, diction, camera emphasis, dramatic effects, source positioning, contextual omission, and post-broadcast counter-framing. The findings show that the broadcast constructed pesantren through a selective frame that foregrounded controversy, hierarchy, and symbolic tension, while giving limited attention to the ethical, pedagogical, cultural, and spiritual meanings of pesantren traditions. Kiai–santri relations were intensified through audiovisual dramatization, whereas concepts such as adab, khidmah, barakah, sanad, and moral discipline received insufficient explanatory space. The study further reveals that the segment reflected attention-oriented corporate media logic, in which sensitive socio-religious issues were packaged as visually and emotionally engaging content. Public criticism, pesantren responses, and regulatory reactions subsequently transformed the broadcast into a wider socio-religious communication event. This study contributes to media framing, media representation, and media–religion scholarship by conceptualizing televised religious controversy as an interaction among textual construction, audiovisual meaning-making, commercial media logic, and public counter-framing within Indonesia’s hybrid media ecology. It also underscores contextual responsibility in representing religious educational institutions in broadcasting.